Comparison of Swine and Human Computational Hemodynamics Models for the Study of Coronary Atherosclerosis - De Nisco, Giuseppe; Chiastra, Claudio; Hartman, Eline M. J.; Hoogendoorn, Ayla; Daemen, Joost; Calò, Karol; Gallo, Diego; Morbiducci, Umberto; Wentzel, Jolanda J. (Frontiers in Bioengineering and Biotechnology, 2021)
Coronary atherosclerosis is a leading cause of illness and death in Western World and its mechanisms are still non completely understood. Several animal models have been used to (1) study coronary atherosclerosis natural history and (2) propose predictive tools for this disease, that is asymptomatic for a long time, aiming for a direct translation of their findings to human coronary arteries. Among them, swine models are largely used due to the observed anatomical and pathophysiological similarities to humans. However, a direct comparison between swine and human models in terms of coronary hemodynamics, known to influence atherosclerotic onset/development, is still lacking. In this context, we performed a detailed comparative analysis between swine- and human-specific computational hemodynamic models of coronary arteries. The analysis involved several near-wall and intravascular flow descriptors, previously emerged as markers of coronary atherosclerosis initiation/progression, as well as anatomical features. To do that, non-culprit coronary arteries (18 right – RCA, 18 left anterior descending – LAD, 13 left circumflex – LCX coronary artery) from patients presenting with acute coronary syndrome were imaged by intravascular ultrasound and coronary computed tomography angiography. Similarly, the three main coronary arteries of ten adult mini-pigs were also imaged (10 RCA, 10 LAD, 10 LCX). The geometries of the imaged coronary arteries were reconstructed (49 human, 30 swine), and computational fluid dynamic simulations were performed by imposing individualized boundary conditions. Overall, no relevant differences in (1) wall shear stress-based quantities, (2) intravascular hemodynamics (in terms of helical flow features), and (3) anatomical features emerged between human- and swine-specific models. The findings of this study strongly support the use of swine-specific computational models to study and characterize the hemodynamic features linked to coronary atherosclerosis, sustaining the reliability of their translation to human vascular disease.